Biophysical, docking, and cellular studies on the effects of cerium oxide nanoparticles on blood components: in vitro - Eskandari N (Dove Medical Press, 2018)
Neda Eskandari,1,* Mohammad Mahdi Nejadi Babadaei,1,* Sanaz Nikpur,2 Ghazal Ghasrahmad,2 Farnoosh Attar,3 Masoumeh Heshmati,1 Keivan Akhtari,4 Seyed Mahdi Rezayat Sorkhabadi,5 Seyyedeh Elaheh Mousavi,5 Mojtaba Falahati6 1Department of Cellular and Molecular Biology, Faculty of Advance Science and Technology, Pharmaceutical Sciences Branch, Islamic Azad University (IAUPS), Tehran, Iran; 2Department of Toxicology and Pharmacology, Faculty of Pharmacy, Pharmaceutical Science Branch, Islamic Azad University (IAUPS), Tehran, Iran; 3Department of Biology, Faculty of Food Industry & Agriculture, Standard Research Institute (SRI), Karaj, Iran; 4Department of Physics, University of Kurdistan, Sanandaj, Iran; 5Department of Pharmacology, School of Medicine, Tehran University of Medical Sciences, Tehran, Iran; 6Department of Nanotechnology, Faculty of Advance Science and Technology, Pharmaceutical Sciences Branch, Islamic Azad University (IAUPS), Tehran, Iran *These authors contributed equally to this work Introduction: The application of nanoparticles (NPs) in medicine and biology has received great interest due to their novel features. However, their adverse effects on the biological system are not well understood. Materials and methods: This study aims to evaluate the effect of cerium oxide nanoparticles (CNPs) on conformational changes of human hemoglobin (HHb) and lymphocytes by different spectroscopic (intrinsic and synchronous fluorescence spectroscopy and far and near circular dichroism [CD] spectroscopy), docking and cellular (MTT and flow cytometry) investigations.Results and discussion: Transmission electron microscopy (TEM) showed that CNP diameter is ~30 nm. The infrared spectrum demonstrated a strong band around 783 cm−1 corresponding to the CNP stretching bond. Fluorescence data revealed that the CNP is able to quench the intrinsic fluorescence of HHb through both dynamic and static quenching mechanisms. The binding constant (Kb), number of binding sites (n), and thermodynamic parameters over three different temperatures indicated that hydrophobic interactions might play a considerable role in the interaction of CNPs with HHb. Synchronous fluorescence spectroscopy indicated that microenvironmental changes around Trp and Tyr residues remain almost unchanged. CD studies displayed that the regular secondary structure of HHb had no significant changes; however, the quaternary structure of protein is subjected to marginal structural changes. Docking studies showed the larger CNP cluster is more oriented toward experimental data, compared with smaller counterparts. Cellular assays revealed that CNP, at high concentrations (>50 µg/mL), initiated an antiproliferative response through apoptosis induction on lymphocytes. Conclusion: The findings may exhibit that, although CNPs did not significantly perturb the native conformation of HHb, they can stimulate some cellular adverse effects at high concentrations that may limit the medicinal and biological application of CNPs. In other words, CNP application in biological systems should be done at low concentrations. Keywords: cerium oxide nanoparticles, human hemoglobin, fluorescence spectroscopy, thermodynamic, circular dichroism spectroscopy, docking, flow cytometry